Fabric phase sorptive extraction coupled with UPLC-ESI-MS/MS method for fast and sensitive quantitation of tadalafil in a bioequivalence study - Sameh A. Ahmed; Ali M. Alalawi; Ahmed M. Shehata; Abdulmalik A. Alqurshi; Yaser M. Alahmadi; Hany S. M. Ali (Elsevier, 2022)
The current study coupled fabric phase sorptive extraction (FPSE) with ultraperformance liquid chromatography method with electrospray ionization and tandem mass detection (UPLC-ESI-MS/MS) for fast and sensitive determination of tadalafil (TAD) in a bioequivalence study. Fabric phase sorptive extraction allowed direct extraction of TAD from the sample matrix with improved selectivity, repeatability, and recoveries. A sol-gel Carbowax 20 M (CX-20 M) coated FPSE membrane revealed the best extraction efficiency for TAD because of its strong affinity for analytes via intermolecular interactions, high mass transfer rate to FPSE membrane, and high permeability. An automated multiple reaction monitoring (MRM) optimizer was employed for the best selection of the precursor and product ions, ion breakdown profile, the fine adjustment of the fragmentor voltages for each precursor ions, and the collision energies for the product ions. The chromatographic separation was conducted using a mobile phase A: 5.0 mM ammonium acetate with 0.1 % formic acid in water and mobile phase B: formic acid (0.1%) in acetonitrile in ratio (55:45, v/v) through isocratic elution mode on an Agilent EclipsePlus C18 (50 × 2.1 mm, 1.8 μm) column and the flow rate was adjusted at 0.4 mL min−1. The total run time per sample was 1.0 min. The method was validated by FDA standards for bioanalytical method validation over a concentration range of 0.1-100 ng mL−1 with a correlation coefficient of 0.9993 and the lower limit of quantitation (LLOQ) was 0.1 ng mL−1 in rat plasma. Intra- and inter-assay precision (%RSD) were lower than 4.1% and accuracy (%RE) was within 2.4%. The developed FPSE-UPLC-ESI-MS/MS method was effectively used in a randomized, two-way, single-dose, crossover study to compare the bioequivalence of two TAD formulations from different companies in male rats and verified to be bioequivalent.